Debt-for-environment swap as a game: The case of the Polish EcoFund - Tomasz Zylicz (Fondazione Eni Enrico Mattei (FEEM), 1998)
Debt swaps as an instrument of international co-operation in environmental field were conceived and first applied in the 1980s. They were once thought of as "win-win" arrangements solving environmental and economic problems at the same time. In the 1990s it became clear, however, that (1) debt-for-environment swaps attracted as little as 1-2 percent of debt swap schemes (with debt-for-equity swaps taking almost all the rest), and (2) the effectiveness and efficiency of those carried out was sometimes problematic. The paper addresses the question of why – despite high expectations – debt-for-environment swaps have not emerged as a major international environmental policy tool. A debt swap is defined as a game. Its players include not only a creditor and a debtor governments (typically represented by finance ministers), but also a number of other stakeholders such as producers of abatement equipment, environmental agencies, and environmental NGOs. Cross-border coalitions may compound the pattern of conflict and co-operation. Issue linkage has been observed too. Specific design of a swap, comprising project selection and procurement rules among other things, determines whose interests are directly served by its mechanism, whose are left to the market forces, and whose are not served at all. Thus alternative design features, discussed in the paper, are reflected in payoffs from the game. The analytical model developed is applied to the Polish debt swap negotiated with the Paris Club in 1991. Under the agreement on the official debt forgiveness (50 percent) and rescheduling, Poland has been authorised to negotiate additional swaps (up to 10 percent) in a series of bilateral and voluntary deals with creditor countries. The government decided to: (1) seek debt-for-environment swaps only, and (2) co-ordinate all the bilateral contracts through a multilateral facility, the EcoFund, operated by the contributing creditor countries and Poland on a "club basis". Even though the EcoFund proved successful in its role serving global environmental protection and creditors' commercial interests, its development has been slow. Two countries took advantage of the full 10 percent swap option, three more participate with lower contributions and few others are still considering their membership in the "club". By referring to the game theoretic model developed, the author offers interpretations of this process.
Keywords: 330; Umschuldung; Umweltabkommen; Spieltheorie; Theorie; Polen